PENGEMBANGAN BUKU PENGAYAAN DIALOG DI LINGKUNGAN KELUARGA BERBASIS UNGGAH-UNGGUH UNTUK SISWA SMP DI KABUPATEN SEMARANG - Nurcahyaningrum, Desiyana Rendryasari (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2018)
This research was based on the lack of the enrichment books containing Javanese language dialogues in accordance with the unggah-ungguh in Semarang regency. Therefore, this study developed the enrichment books of dialogue in family environment based on unggah-ungguh to support the studying and writing dialogue text. This study used research and development design. The research data was the data of teacherÃ¢â‚¬â„¢s and studentÃ¢â‚¬â„¢s needs, expert validation, and product trials. The result of this study was the enrichment book containing collection of dialogues in the family environment based on unggah-ungguh with the title Ã¢â‚¬Å“Tepa PalupiÃ¢â‚¬Â. The book had improved after being validated by expert lecturers and users. Experimental result showed that the enrichment book of dialogue in family environment based on unggah-ungguh can improve student achievement. The test results on the examining dialogue text competence increased 7,4%, where as the writing dialogue text competence increased 17.2%. The improvement was followed by an attitude of students to be more active, enthusiastic, and very interested in reading the enrichment books used in the learning. Keywords: the enrichment books, dialogue, family environment, unggah-ungguh